Prevalence of workplace violence among healthcare workers in a health district in Selangor and its associated factors - Ibrahim, Mohd Safwan (2017)
Introduction: Workplace violence is incident where staff are abused, threatened or assaulted in circumstances related to their work, including commuting to and from work, involving an explicit or implicit challenge to their safety, well-being or health. It can be as mild as verbal abuse to a very serious condition such as homicide. Currently, there is no well establish reporting system or surveillance in healthcare setting specifically on workplace violence especially for violence which did not cause any physical injury. Published research on prevalence of healthcare workplace violence in Malaysia is very limited and only focus on nurses especially in the hospital.